Faktor Yang Mempengaruhi Agresivitas Pajak Perusahaan Manufaktur Yang Terdaftar Di BEI - Agnes Priscilia Yauris, Sukrisno Agoes (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This research was conducted to determine the effect of company size, profitability and managerial ownership on tax aggressiveness. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange during the period 2015-2017. Sampling of this study was based on purposive sampling. The sample used in this study was 40 companies. Data from each research object are obtained from financial statements and annual reports as of December 31 for the period 2015-2017 obtained from the Indonesia Stock Exchange through the website www.idx.co.id. The results of this study indicate that profitability has a significant and positive effect on tax aggressiveness while firm size and managerial ownership have no significant effect on tax aggressiveness